2013
DOI: 10.1021/ic401753y
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, and Magnetic Properties of Four New Cyano-Bridged Bimetallic Complexes Based on the mer-[FeIII(qcq)(CN)3] Building Block

Abstract: Four new cyano-bridged bimetallic complexes, [{Mn(III)(salen)}2{Fe(III)(qcq)(CN)3}2]n·3nCH3CN·nH2O (1) [salen = N,N'-ethylenebis(salicylideneiminato) dianion; qcq(-) = 8-(2-quinoline-2-carboxamido)quinoline anion], [{Mn(III)(salpn)}2{Fe(III)(qcq)(CN)3}2]n·4nH2O (2) [salpn = N,N'-1,2-propylenebis(salicylideneiminato)dianion], [{Mn(II)(bipy)(CH3OH)}{Fe(III)(qcq)(CN)3}2]2·2H2O·2CH3OH (3) (bipy = 2,2'-bipyridine), and [{Mn(II)(phen)2}{Fe(III)(qcq)(CN)3}2]·CH3CN·2H2O (4) (phen = 1,10-phenanthroline) have been synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The Fe atom is complexed by three CN groups and three N donors of qxcq in a meridional configuration, forming octahedral coordination geometry. The Fe–C bonds are in the normal range compared with other reported mer -tricyanoiron(III) precursors [24,25,26,27,28,29,30,31,32,33,34]. One of the three Fe–N amide bond lengths with the value 1.945(5) Åwas slightly shorter than the other ones (2.004(5)–2.060(5) Å) relevant with qxcq, which can be attributed tothe strong σ-donor influence of the deprotonated amide ligand.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The Fe atom is complexed by three CN groups and three N donors of qxcq in a meridional configuration, forming octahedral coordination geometry. The Fe–C bonds are in the normal range compared with other reported mer -tricyanoiron(III) precursors [24,25,26,27,28,29,30,31,32,33,34]. One of the three Fe–N amide bond lengths with the value 1.945(5) Åwas slightly shorter than the other ones (2.004(5)–2.060(5) Å) relevant with qxcq, which can be attributed tothe strong σ-donor influence of the deprotonated amide ligand.…”
Section: Resultsmentioning
confidence: 74%
“…Up to now, many 0D discrete clusters and 1D infinite coordination polymers have been successfully obtained by assembling the decorated polycyanometallates such as the blocked trans -dicyano-, fac -tricyano-, mer -tricyano- and tetracyanometallate, and the paramagnetic compound with or without the auxiliary ligand [18,19,20,21,22,23]. Several reports from our and other groups on the mer -[Fe(L](CN) 3 ] -/2- -based cyanide-bridged complexes, where L represents the equatorial in-plane ligands with relative large steric effect for efficiently lowering the dimensionality of the target complex such as bis (2-pyridylcarbonyl)amidate (bpca) [24,25], 8-(pyridine-2-carboxamido)quinoline (pcq) [26,27,28], 8-(pyrazine-2-carboxamido)quinoline (pzcq) [29], 8-(5-methylpyrazine-2-carboxamido)quinoline (mpzcq) [30], 8-(2-quinoline-2-carboxamido)quinoline (qcq) [31], N -(quinolin-8-yl)isoquinoline-1-carboxamide anion (iqc) [32], and bis (2-benzimidazolyl)pyridine (bbp) [33,34] showed that the mer -[Fe(L](CN) 3 ] -/2- type precursors are excellent candidates for constructing interesting magnetic assemblies. Here, a new structurally characterized mer -tricyanoiron(III) building block 1 (Scheme 1) was first employed to assemble with the manganese Schiff base compounds (Scheme 1), leading to a series of new CN-bridged Fe(III)-Mn(III) complexes with various structural types formulated as {[Fe(qxcq)(CN) 3 ][Mn(L 1 )(H 2 O)]}[Mn(L 1 )(H 2 O)(CH 3 OH)](ClO 4 )·1.5MeOH·0.5H 2 O (L 1 = N,N′-bis (3-methoxy-5-bromosalicylideneiminate) (2), {[Fe(qxcq)(CN) 3 ][Mn(L 2 )]} 2 ·0.5H 2 O (L 2 = N,N′ -ethylene- bis (3-ethoxysalicylideneiminate)) (3), [Fe(qxcq)(CN) 3 ][Mn(L 3 )] (L 3 = bis (acetylacetonato)ethylenediimine) (4), and [Fe(qxcq)(CN) 3 ][Mn(L 4 )]·1.5MeOH·0.5CH 3 CN·0.25H 2 O (L 4 = N,N′ -(1,1,2,2-tetramethylethylene)bis(salicylideneiminate)) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the coupling constant is contingent on the Mn-NuC bending in the bridging pathway. [25][26][27][28][29][30][31][32][33][34] In comparison, mer-Fe tricyanides have been developed to collect information on basic magnetic properties. The Fe precursors have been used to react with anisotropic Mn(III) Schiff bases, leading to the formation of Mn(III)-Fe(III) bimetallic chain complexes with molecular or one-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%